An overview of recent technique and the affecting parameters in the demulsification of crude oil emulsions - Saad, M. A.; Nour, A. H.; R. M., Yunus; H. S., Ali (IOP Publishing, 2020)
The crude oil mix with water through processing and under significant shear at the wellhead and with the assistance of surface-active substance which is present naturally in the crude oil leading to the formation of water-oil emulsions. These emulsions are undesirable and cause problem like pipeline corrosion, pump malfunctions, poisoning of downstream refinery catalysts, and other problems. Emulsions are needed to demulsify and separate the water. There are various parameters related in crude oil demulsification that can both reduce or rise the stability of the emulsion by altering each. Therefore, this study presents an overview of research efforts on the state-of-the-art demulsification techniques through the last years and the parameters affecting the demulsification process. Firstly, an overview of the crude oil emulsion, kinds, formation, and stability. After that, a short discussion of the different demulsification techniques process. Finally, the study of the parameters affecting the demulsification process, including salinity, temperature, pH, water content, and emulsifier / demulsifier dose. The review of literature culminated in the proposition for future research.